Moving with the times in search of permanence: The digitization of “liberation struggle” archives in southern Africa (Historia, 2021)
The struggle to liberate the continent of Africa from colonialism was a profound and all-time consuming one for Africans during the second half of the twentieth century and as such, this history needs to be documented accurately in whatever form for the benefit of posterity. Amaral Cabral opined that the people's struggle for national liberation and independence from imperialist rule constituted one of the essential characteristics of contemporary history.
Keywords: Africa; colonialism; digitization; transformation in heritage institutions; information and communication technologies; drawbacks and the benefits; technical and policy overview; “liberation struggle” archives